2013
DOI: 10.1071/pc130121
|View full text |Cite
|
Sign up to set email alerts
|

The breeding biology of the Forest Red-tailed Black Cockatoo Calyptorhynchus banksii naso Gould in south-western Australia. I. Characteristics of nest trees and nest hollows.

Abstract: The Forest Red-tailed Black Cockatoo Calyptorhynchus banksii naso (FRTBC) is a large, iconic forest cockatoo, endemic to the south-west corner of Western Australia. It is currently listed as Vulnerable under the State Western Australian Wildlife Conservation Act and under the Commonwealth Environment Protection and Biodiversity Conservation Act. In this paper, we provide details of nest tree and nest hollow requirements based on details of hollows in 128 nest trees studied over 17 years. FRTBC are monogamous a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…The FRTBC form monogamous pairs, and after breeding occurs, the juveniles are dependent on the parents for roughly eighteen months to two years after fledging (Johnstone et al. ). Previous studies have shown that breeding occurs across all months of the year with peaks in autumn (April–June) and spring (August–October) and breeding frequency varies significantly between years (Johnstone et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The FRTBC form monogamous pairs, and after breeding occurs, the juveniles are dependent on the parents for roughly eighteen months to two years after fledging (Johnstone et al. ). Previous studies have shown that breeding occurs across all months of the year with peaks in autumn (April–June) and spring (August–October) and breeding frequency varies significantly between years (Johnstone et al.…”
Section: Introductionmentioning
confidence: 99%
“…The FRTBC is a highly mobile species, and previous studies have reported that the adults travel long distances (>20 km/d) from their nests in search of food and water, and these movements are changing due to altered water and food availability in SWWA forests (Johnstone et al 2013a). The FRTBC form monogamous pairs, and after breeding occurs, the juveniles are dependent on the parents for roughly eighteen months to two years after fledging (Johnstone et al 2013b). Previous studies have shown that breeding occurs across all months of the year with peaks in autumn (April-June) and spring (August-October) and breeding frequency varies significantly between years (Johnstone et al 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, since suitably sized nesting hollows for black cockatoos generally occur in trees aged 130-200+ years old (Whitford and Williams 2002;Johnstone et al 2013a), the trees at our sites have not yet developed suitable nesting hollows.…”
Section: Management Implicationsmentioning
confidence: 99%
“…Habitat loss is a major threat to the survival of the three black cockatoos endemic to south-western Australia (the forest red-tailed black cockatoo (Calyptorhynchus banksii naso; FRTBC), Carnaby's cockatoo (Calyptorhynchus latirostris; CBC), and Baudin's cockatoo (Calyptorhynchus baudinii; BBC) (Chapman 2008;Garnett et al 2011;Department of Environment 2012;Johnstone et al 2013aJohnstone et al , 2013b. All three species of cockatoo are listed as threatened under the Commonwealth Environment Protection and Biodiversity Conservation Act 1999, whereas CBC and BBC are classified as Endangered in the IUCN Red List (Birdlife International 2013a.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation